0053 Circadian and Reward Measures Show Robust Bidirectional Relationships in Bipolar Spectrum Disorder in a 20-Day Naturalistic Ecological Momentary Assessment Study. (27th April 2018) - Alloy, L B; Ng, T H; Titone, M K; Dennis, L E; Goel, N
Abstract: Introduction: Adolescence/early adulthood is an "age of risk" for bipolar spectrum disorders (BSDs). BPDs have been linked to circadian rhythm and reward processing disruptions; such disruptions may serve as risk factors for BSD mood symptoms/ episodes: However, the bidirectional relationships of the circadian and reward systems have not been systematically examined in BSD or at-risk individuals. Methods: 150 adults (ages 18–27; mean age ± SD, 21.9 ± 2.1y; 88 women), with high reward sensitivity and a BSD (n = 43), at-risk with high reward sensitivity but no BSD (n = 64), and low-risk individuals with moderate reward sensitivity and no BSD (n = 43) participated in a 20-day naturalistic ecological momentary assessment (EMA) study, involving 3 phases: 1. Baseline; 2. Goal striving and 3. Goal/reward outcome. Salivary dim light melatonin onset (DLMO) was assessed as a circadian phase marker in each phase and the Morningness-Eveningness Questionnaire (MEQ) assessed chronotype. The Willingly Assumed Set of Statistically Unlikely Pursuits assessed ambitious goal striving, the UPPS Sensation-Seeking subscale determined sensation seeking, and the Card Arranging Reward Responsivity Objective Test and SPSRQ Sensitivity to Reward subscale measured reward responsiveness and sensitivity, respectively. The Barratt Impulsiveness Scale evaluated impulsivity. Pearson's correlations were used for statistical analysis. Results: Baseline DLMO positively correlated with goal striving (r=0.202, p<0.05) and sensation seeking (r=0.543, p<0.001), and with reward sensitivity ratings and reward-relevant events (r's=0.359–0.457, p<0.005). MEQ negatively correlated with goal striving (r= -0.135, p<0.05) and impulsivity (r= -0.174, p<0.005). Notably, these relationships were maintained during the goal striving and reward outcome phases, indicating their stability across time. Conclusion: Our results demonstrate for the first time that a number of validated circadian and reward measures have robust bidirectional relationships in BSD, whereby measures of greater eveningness/later phase (MEQ and DLMO) are related to greater reward sensitivity across various dimensions. Support (If Any): This work was supported by NIH R01 MH102310.